Cobalt-modified palladium nanocatalyst on nitrogen-doped reduced graphene oxide for direct hydrazine fuel cell. Issue 62 (8th December 2021) - Hosseini, Mir Ghasem; Daneshvari-Esfahlan, Vahid; Wolf, Sigrid; Hacker, Viktor
Abstract : The superior catalytic activity and stability of a novel anodic PdCo NPs/NrGO NSs for HzOR are confirmed by half and signal cell investigations. Abstract : Nitrogen-doped reduced graphene oxide-supported palladium–cobalt nanoparticles (PdCo NPs/NrGO NSs) are synthesized and used as a high-performance and low-cost anodic catalyst for direct hydrazine–hydrogen peroxide fuel cells. The SEM and TEM images of PdCo NPs/NrGO NSs show the uniform metal nanoparticle distribution on the NrGO NSs. The reduction of the oxygen functional groups and the doping of the nitrogen atoms in the GO framework are confirmed by FT-IR and XRD spectroscopic studies. The Pd catalysts modified by Co exhibit a higher catalytic activity, lower onset potential, better durability, and lower impedance values than unmodified Pd catalysts for the electro-oxidation of hydrazine. The kinetic studies show a first-order reaction with an activation energy of 12.51 kJ mol −1 . A direct hydrazine–hydrogen peroxide fuel cell with PdCo NPs/NrGO NSs as anode and Pt/C as cathode provides an open circuit voltage of 1.76 V and a maximum power density of 148.58 mW cm −2 at 60 °C, indicating that the PdCo NPs/NrGO NSs are an economical, high performance and reliable anode catalyst for the direct hydrazine–hydrogen peroxide fuel cell.